Guinness world records 2012 - Glenday, Craig; Guinness World Records Limited ([London] Guinness World Records, 2011)
Lists records, superlatives, and unusual facts in the areas of fame, business, crime, the natural world, technology, war, the arts, music, fashion, and sports.
Universe -- Planet Earth -- Variety of life -- Time tales -- Human body -- Skills & talents -- Spirit of adventure -- Society -- Sci-tech & engineering -- Popular culture -- Sports.
Keywords: World records; Curiosities and wonders